Influence of main operating conditions on contact wire wear of rigid catenary lines - Simarro, Monserrat; Postigo-Pozo, Sergio; Casanueva, Carlos; Rodriguez-Tembleque, Luis; Castillo-Aguilar, Juan Jesús (Elsevier, 2024)
A validated overhead conductor rail and a well-known wear model have been programmed to perform closer-to- reality simulations. Reliable wear rate estimates for two configurations of overhead conductor rails and three models of pantographs at different speeds and supply currents have been obtained. Results show that wear decreases with increasing speed at high currents and when the distances between supports are uniform. In addition, the use of different types of pantographs in the same facility has a positive effect in terms of wear reduction. Consequently, an adequate selection of the operating conditions contributes to reducing the wear rate
Keywords: Transporte ferroviario; Ferrocarriles-tecnología; Ferrocarriles-equipo y material; Wear; Contact forces; Overhead conductor rail (OCR); Pantograph